Exploring SME owners’ motivation to learn and acquire new skills for the adoption of e-commerce - Naledi D.D. Gallant; Anthea P. Amadi-Echendu; Elriza Esterhuyzen (The Southern African Journal of Entrepreneurship and Small Business Management)
Background: The adoption of e-commerce among Soweto-based small and medium-sized enterprises (SMEs) is crucial for their growth and competitiveness. Traditional approaches in determining factors that motivate the adoption of e-commerce have been mainly quantitative, not taking into consideration the experiences, motivation and perceptions of SME owners’ willingness to learn and acquire new skills for the adoption of e-commerce.